2020
DOI: 10.1155/2020/2904789
|View full text |Cite
|
Sign up to set email alerts
|

Layered Grouting Technology Based on a Comprehensive Water‐to‐Cement Ratio for the Overlying Loess Stratum of Urban Shallow Tunnels

Abstract: Different from sand and clay, loess has special engineering properties; hence, existing soil grouting theories are not suitable for the disaster treatment of shallow loess tunnels. In this study, a fine grouting reinforcement test system was developed, and the Yuhan Road tunnel overlying loess was used as the injection medium. An orthogonal test based on slurry dry density, moisture content, water-to-cement ratio, and grouting pressure was conducted. Results revealed that the loess samples have high integrity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The analysis of the effect of grouting under different working conditions shows that the factors influencing the compressive strength of the solidified soil in order are: service environment > water content > dry density. Yang [ 45 ] studied the effects of dry density of loess, water content, water–cement ratio, and grouting pressure on the reinforcement effect, and concluded that water–cement ratio and water content were the main controlling factors. The service environment was introduced in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the effect of grouting under different working conditions shows that the factors influencing the compressive strength of the solidified soil in order are: service environment > water content > dry density. Yang [ 45 ] studied the effects of dry density of loess, water content, water–cement ratio, and grouting pressure on the reinforcement effect, and concluded that water–cement ratio and water content were the main controlling factors. The service environment was introduced in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the longitudinal profile of the tunnel. 2020) established a precise grouting reinforcement test system, using the Yuhang Road tunnel with overlying loess as the injection medium, and conducted an orthogonal test based on slurry dry density, moisture content, water-cement ratio, and grouting pressure [19].…”
Section: Supporting Projectsmentioning
confidence: 99%
“…Fan, H. et al (2023) analyzed the settlement of tunnel bedrock and the structural mechanical response characteristics under the influence of jet grouting piles with different lengths and diameters in weak loess areas using centrifugal model tests, effectively reducing tunnel bottom settlement and significantly shortening the stress adjustment time of surrounding rocks [18]. Yang, T. et al (2020) established a precise grouting reinforcement test system, using the Yuhang Road tunnel with overlying loess as the injection medium, and conducted an orthogonal test based on slurry dry density, moisture content, water-cement ratio, and grouting pressure [19].…”
Section: Introductionmentioning
confidence: 99%